Formulation And Evaluation Of Taste Masked Dispersible Tablets Of Zidovudine - YASH PAUL; SARVAN TYAGI; BHUPINDER SINGH (International Journal of Pharma and Bio Sciences, 2011)
Zidovudine is an antiretroviral drug commonly used in the treatment HIV infection. But it is very bitter in taste and sparingly soluble in water. Thus the purpose of this investigation was to formulate and evaluate taste masked dispersible tablets of zidovudine. Dispersible tablets of zidovudine were prepared using crosscarmellose sodium (Ac-di-sol) as disintegrant. Surelease clear (E-7-19010) in concentration range of 0.044mL/tab to 0.052mL/tab completely masked the taste of zidovudine. The prepared tablets were evaluated for general appearance, drug content, weight variation, thickness, hardness, friability, taste evaluation, mouth feel, in vitro dispersion time and in vitro dissolution studies. Tablet formulations showed quick disintegration time, which is very characteristic of dispersible tablets. Results revealed that the tablets containing taste enhancers and surelease as binder had a good palatability. Oral dispersible tablets prepared using Surelease 0.044mL/tablet and Ac-di-sol 6% possessed least disintegration time (18.9), pleasant taste and offered better dissolution profile than that of all other dispersible tablet formulations developed in the present investigation and that of marketed conventional tablet formulation of zidovudine.